التعرية في حوض وادي "تلێ" باستخدام نظم المعلومات الجغرافية"Gis "دراسة جيومورفولوجية تطبيقية - محمد, خليل كريم (Sulaimani Journal for Humanities, 2018)
The study area is located at the south-western part of Sulaymaniyah Governorate between latitude lines (°35 ̋ 20 '37 and °35 ̋ 27 ʹ40 N) and longitudinal lines (°45 "11 "32 and ° 45 "23 ʹ29 E) and covers about (204.5 km2). There are numbers of villages within this area built around existing natural springs. This area surrounded by numbers of mountain ranges, Bazian and Darikali from the northern side and the Baranan with Glazarda from the east, from the south part the area surrounded by Sagirma mountain range which considered a dividing line between Tili basin and Garmian basin. The high land on the south-western part of the studied area is the divide line between Tili and Diwana Basin. Topographically the study area elevation ranges between (671 to 1698) meter above sea level and the slope of the area is between (0° - 54°) which effects on erosion in the study area. The studied area characterized with a relatively dense vegetation cover which reduces the effect of water or wind erosion processes. The analysis process of water and wind erosion in Wadi Tali basin appear that water erosion is the most significant in compare to other erosion processes. Applying Birgismas Law appears that the valley erosion is about (239413.89) m for the area and the water erosion in accordance with the Douglas law was 6.78 m / km2 / year. The mean rain capacity in the study area was 90.27 degrees, which is a moderate capacity according to the Fournier index for the classification of the rain capacity, while the wind capacity which based on Chepil equation is (11.39) and is very light.